Pengaruh Konsentrasi EM4 Yang Berbeda Pada Fermentasi Bungkil Inti Sawit Penyusun Pakan Terhadap Konversi Pakan dan Pertumbuhan Ikan Nila (Oreochromis niloticus) - Simarmata, Daniel Pandapotan; Kusdianto, Heru; Rizal, Samsul (Universitas Batangahari Jambi, 2024)
Tilapia fish (Oreochromis niloticus) has advantages for cultivation compared to several other freshwater fish However, the high price of fish feed causes the costs incurred by fish farmers to increase, therefore it is necessary to look for alternative feed ingredients. One of the ingredients for alternative feed that is abundant, high quality and easy to obtain is Palm Kernel Meal (PKM). The purpose of this research was to analyze the nutritional value of artificial feed made from palm kernel cake as the main ingredient fermented using EM4 with different concentrations and to analyze its effect on feed conversion, absolute weight growth and daily growth rate of Tilapia (Oreochromis niloticus). This research used a Completely Randomized Design (CRD) with 3 treatments and 4 replicates each. The treatments applied were unfermented palm kernel meal (P1), fermented palm kernel meal with a concentration of 4 ml/kg (P2), and fermented palm kernel meal with a concentration of 8 ml/kg (P3). The results of the proximate analysis of the feed showed that the protein content of the feed was 30.37 %, 30.17 % and 30.87 % for P1, P2 and P3 respectively. Meanwhile, the lipid content of feed P1, P2, and P3 is 3.00%, 9.04%, and 8.54% respectively. Another finding in this research was that the highest growth was produced by treatment P3 (46.33 g) and this was followed by treatments P2 (41.25 g) and P1 (36.68 g). Meanwhile, the calculation results showed that the best feed conversion ratio was produced by treatment P3 (2.13) and then followed by P2 (2.34) and P1 (2.78). An increase in feed lipid content which causes an increase in feed energy content is thought to increase the efficiency of protein use to support growth and reduce the feed conversion ratio value.